Case Report: Functional MR imaging of alveolar soft part sarcoma - Li, Jie; Yang, Zhaoyang; Jiang, Jiuming; Gong, Lihua; Li, Meng (Frontiers in Oncology, 2025)
This study presents a rare case of acinar soft tissue sarcoma and provides a detailed analysis of its multi-parameter quantitative functional MRI (fMRI) characteristics. The patient, a 16-year-old male, was diagnosed with acinar soft tissue sarcoma after presenting with a progressively enlarging mass in the right thigh. To determine the extent and nature of the lesion, MRI examinations were performed using conventional plain scans, contrast-enhanced scans, dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI), and intravoxel incoherent motion (IVIM) for quantitative analysis. Functional MRI imaging not only provides crucial diagnostic and differential diagnostic information for acinar soft tissue sarcoma, but also reveals through DCE-MRI and IVIM imaging indicators that ASPS exhibits high cellular density, increased vascular permeability, and abundant neovascularization. The local microcirculation characteristics offer vital insights into the tumor’s biological behavior and prognosis. Furthermore, functional MRI aids in precise diagnosis while providing references for surgical planning, postoperative adjuvant therapy, long-term follow-up evaluation, and recurrence risk prediction.